Production and extraction of carotenoids produced by microorganisms - Mussagy, Cassamo Ussemane [UNESP]; Winterburn, James; Santos-Ebinuma, Valéria Carvalho [UNESP]; Pereira, Jorge Fernando Brandão [UNESP] (Springer Nature, 2019)
Carotenoids are a group of isoprenoid pigments naturally synthesized by plants and microorganisms, which are applied industrially in food, cosmetic, and pharmaceutical product formulations. In addition to their use as coloring agents, carotenoids have been proposed as health additives, being able to prevent cancer, macular degradation, and cataracts. Moreover, carotenoids may also protect cells against oxidative damage, acting as an antioxidant agent. Considering the interest in greener and sustainable industrial processing, the search for natural carotenoids has increased over the last few decades. In particular, it has been suggested that the use of bioprocessing technologies can improve carotenoid production yields or, as a minimum, increase the efficiency of currently used production processes. Thus, this review provides a short but comprehensive overview of the recent biotechnological developments in carotenoid production using microorganisms. The hot topics in the field are properly addressed, from carotenoid biosynthesis to the current technologies involved in their extraction, and even highlighting the recent advances in the marketing and application of “microbial” carotenoids. It is expected that this review will improve the knowledge and understanding of the most appropriate and economic strategies for a biotechnological production of carotenoids.
Keywords: Biotechnology; Carotenoids; Extraction; Market; Microorganisms; Production